2011
DOI: 10.1007/s00167-011-1806-4
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic postural control in competitive athletes after anterior cruciate ligament reconstruction and controls

Abstract: Prognostic study, case-control, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 40 publications
1
59
1
3
Order By: Relevance
“…Only one study [36] observed a greater KAM in an ACLR group during a side hop (6.96 vs. The other eleven studies investigated biomechanical variables in the context of stability and postural control [37][38][39][40], gait [41], vision [42], limb asymmetry [43], walk and jog patterns [44], gender differences [45], as well as neuromuscular aspects [46]. Landing strategies and medio-lateral control of the ACLD and ACLR patients were also investigated by Roos et al [47] and found that these groups had not fully recovered.…”
Section: Level 2 Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Only one study [36] observed a greater KAM in an ACLR group during a side hop (6.96 vs. The other eleven studies investigated biomechanical variables in the context of stability and postural control [37][38][39][40], gait [41], vision [42], limb asymmetry [43], walk and jog patterns [44], gender differences [45], as well as neuromuscular aspects [46]. Landing strategies and medio-lateral control of the ACLD and ACLR patients were also investigated by Roos et al [47] and found that these groups had not fully recovered.…”
Section: Level 2 Evidencementioning
confidence: 99%
“…Distinguishing characteristics of ACLD groups included posterior centre of mass (COM) changes [39], increased time to stabilization [40], postural sway and other unique adaptations aimed at stabilizing the knee [46]. Distinguishing characteristics of ACLR groups included greater postural sway [37] and altered responses to visual disruption [42].…”
Section: Level 2 Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to mechanical instability, ACL rupture inescapably displays reduced knee proprioception due to disruption of mechanoreceptors within the ligament (4). Disruption to both the sensory feedback and mechanical restraint role of the intact ACL following ACL rupture may result in impaired lower limb function and impaired postural control (5).…”
Section: Introductionmentioning
confidence: 99%
“…Tasks that challenge the control of standing balance, by altering support surfaces and stance positions, are reported to provide predictable changes in performance and suggested to evaluate the postural control (5). Disturbance of dynamic postural control, between the two limbs of ACL-reconstructed group and between the ACL-reconstructed subjects and control group are reported (1,5). Assessing the postural control is frequently done by manipulation of size support area and perturbations of the base of support.…”
Section: Introductionmentioning
confidence: 99%